COMMUNICATING PRE- OPERATIVE INSTRUCTIONS - Sheehan, Kim (Operating Room Nurses Association of Canada Journal, 2005)
Effective communication is a pivotal component of pre-operative teaching. The writer will discuss the factors that may affect client learning and the importance of the nursing process in pre-operative teaching.